Parcerias entre Estado e Terceiro Setor em Angola: a Organização Não Governamental - ADRA - um estudo de caso - Quitombe, Cecília José (2015)
The topic of this study is the third sector in the management of social programs in partnership with the State . The objective of the study is to analyze the partnership between the State and the third sector in the management of social programs in Angola in the post-conflict context. Between 1975-2002, Angola faced a civil that to some extent weakened the relationship between the State and the civil society. To characterize the peace scenario and the changes that occurred during these years is fundamental if it is taken into account the social problems that the country faces. Thenon governmental organizations, on their turn, had to change their strategies of intervention by adjusting it to the development phase. The study looked at ADRA, as the case study, that enabled us to carry out the qualitative approach through an archival and bibliographical research. The key concepts applied to study are partnership, social programs, State, and communitarian development. It was learnt that the partnership between the State and ADRA happen at different levels depending on the administrative organization the State ( Municipalities, Provinces and Central/National). Therefore, at each level, ADRA adapts itself and sets its programs and projects, the partnerships and understands this partnerships as actions aimed at complementing the actions of the State. For the third sector, the efficacy of the partnership with the State demands a better adjustment of the principles of participations and democracy in the country